P140 Hypoxic challenge testing in motor neurone disease. (15th November 2017) - Cliff, IJ; Mustfa, N; Stone, H
Abstract : Introduction: Respiratory muscle weakness is a feature of motor neurone disease (MND), develops insidiously and presents with subtle symptoms. It can be difficult to assess in MND patients who, as a result, may be at risk of desaturation at altitude. Hypoxic challenge tests (HCT) can identify patients who would benefit from in-flight oxygen, but evidence as to which patients should be referred is lacking. The aim of this study was to identify factors that may predict the need for in-flight oxygen in this group of patients where maintaining their independence for as long as possible is paramount. Methods: 81 consecutive HCT's in 53 male, 28 female patients, and the contemporaneous assessments for respiratory muscle weakness on patients with MND. Data from patients requiring in-flight oxygen according to the HCT was compared to data from patients who did not, in accordance with the BTS Guidance for Air Travel 2011. Results: The median patient age of patients who passed the HCT was 62 years; those that failed the HCT were significantly older with a median age of 68 years (p=0.009). There was a significant difference in baseline PaO2 and PaCO2 between the groups as shown in Table 1 ; patients who passed the HCT had higher baseline Pa02 and lower PaC02 (10.4 kPa and 5.3 kPa versus 9.3 kPa and 6.2 kPa respectively p=0.0001 and 0.0014). No other parameter, including BMI, smoking history, or physiological measurement including SNIP, or spirometry, could predict the outcome of the HCT. Conclusions: Although MND patients that are likely to fail a HCT have a higher baseline C02, a threshold C02 value that could identify patients needing in-flight oxygen was not determined. We recommend that the safest approach is to refer all patients with MND that intend to fly for HCT assessment until more evidence-based data is available, which is the current practice at this regional centre.